Analisis Keunggulan dan Kelemahan Metode Tilawati dalam Pembelajaran membaca Al-Qur’an Santri - Alfauzan Amin; Muhammad Agus Ainur Rasyid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the problems faced by Al-Qur'an teachers is overcoming student indiscipline in the learning process and challenges in terms of understanding. The impact of these problems resulted in the quality of students' reading decreasing and it took a long time and many students even left before they were able to read the Koran in tartil. The Tilawati method is a learning method that is widely used by various groups to overcome these problems. Based on this argument, researchers feel the need to analyze more deeply the advantages and disadvantages of the method of learning to read the Al-Qur'an using the Tilawati method, with the hope of finding scientific answers regarding why they chose to use the Tilawati method. The results of this research are that there are several advantages of the Tilawati Method, namely, 1) The existence of supporting tools for learning Al-Qur'an, the Tilawati method is equipped with several efficient and effective learning media, 2) Equipped with rost songs from volumes 1-6 and using nahawan songs for development, 3) Learning media in the form of tilawati displays starting from volumes 1-6, 4) Equipped with learning cassettes from volumes 1-6, 5) Applying classical-individual learning strategies in a balanced and proportional manner, so that teaching and learning is more efficient, and student management becomes better. Meanwhile, the disadvantages of the Tilawati Method are: 1) Teachers who will use this method must take part in training and read tartil, 2) With the rost song rhythm approach used in this method, it is feared that it will not be maintained intensively, 3) For letters whose pronunciation is quite difficult no approach is allowed, so from the start students must be able to pronounce the letters well, correctly and fluently, 4) It takes a long time to be able to read the Qur'an, because it has to be done with recitations at the same time.